Intensified Cold Pool Dynamics Under Stronger Surface Heating. Issue 12 (23rd June 2018) - Haerter, Jan O.; Schlemmer, Linda
Abstract: The observed increase of convective extreme precipitation intensities with temperature beyond the Clausius‐Clapeyron rate has recently directed attention to nonequilibrium processes that might cause the increase. While out‐of‐equilibrium simulations with perturbed heating conditions show clear increases in convective precipitation intensities, it has so far remained unclear, to which extent precipitation intensities can increase, when the atmosphere is in "perpetual equilibrium" (PE). We use the term PE to describe periodically forced diurnal cycles that eventually yield an approximately repetitive atmospheric response from day to day. In PE, as defined here, precipitation extremes increase at rates beyond the Clausius‐Clapeyron rate. When analyzing causes for the increase, we find the variance in near‐surface temperature to increase significantly as precipitation builds up throughout the day and that this temperature variance is larger when surface heating is increased. We propose that enhanced rain evaporation may drive a feedback, by which cold pool activity, and the possible collision of cold pool gust fronts, is strengthened—thereby intensifying subsequent convective updrafts and their precipitation. Plain Language Summary: In recent years it has become evident that extreme rain events from thunderstorms react strongly to temperature changes, so that higher temperatures come with much more intense rain—increasing the risk of floods. The origin of the strong temperature sensitivity has so far not been clear. We here propose that the dynamics of the atmosphere is intensified by enhanced rain evaporation, where it falls through the subcloud layer. The effect of this is more cooling below precipitating clouds, leading to larger inequality of temperatures near the surface when comparing cloudy and cloud‐free areas. Where near‐surface air is cold, it is also denser, and this is called a cold pool . It is known that cold pools spread more rapidly along the surface when the lateral temperature difference increases. We here show that this is indeed the case in numerical experiments, as the surface is heated more strongly from one experiment to the next. The implication is that the dynamics of the atmosphere becomes more violent and cold pools, where they collide, can trigger new and stronger subsequent precipitation events. We thereby point to a new feedback, potentially relevant for extreme rain events in a changing climate. Key Points: In perpetual equilibrium, convective precipitation extremes increase beyond the Clausius‐Clapeyron rate The variance of the boundary layer temperature distribution is enhanced at higher surface temperature forcing, implying stronger cold pools A dynamical feedback leading to the observed super Clausius‐Clapeyron increase is suggested